Determination of individual I(V) characteristics of each sub-cell of a triple junction device - Longeaud Christophe; Alvarez José; Fanevamampiandra Herinirina; Bidaud Thomas; Hamon Gwenaëlle; Darnon Maxime; Gueunier-Farret Marie-Estelle (EPJ Photovoltaics, 2023)
Very high conversion efficiency is reached with triple junction solar devices integrated in concentrator photovoltaic (CPV) modules. However, reduction of the active area for micro-CPV applications increases the perimeter/area ratio, enhancing losses linked to the edges. It is therefore important to characterize the perimeter influence on the final conversion efficiency. For this purpose, I(V) characterization under dark and/or light could be used as a test of the sidewalls influence. We have designed an experiment to perform I(V) curves using the light of three lasers with adjustable powers at 405, 785, and 980 nm, preferentially absorbed by the top, middle or bottom junction of the device, respectively. This experiment was applied to commercial devices made from a stack of GaInP/GaAs/Ge. In parallel we have developed a numerical calculation modeling the device to reproduce the behaviors observed during I(V) experiments. Junction parameters and influence of leakage resistances are deduced from the fit of experimental results with the numerical calculation. The I(V) experiment as well as the numerical calculation are presented in details. It is also underlined that, combining both experiment and calculation, the I(V) characteristic of each junction as if it was isolated can be determined.